Holy Saturday Between the Sublime and Beautiful: Fantastic Realism in Kristeva and Desmond's Dostoevskian Ideal - Deckard, Michael (Labyrinth, 2021)
This article examines Dostoevsky's "fantastic realism," which challenges the explanation of rationalism or empiricism in the need for determinate categories fixed in nature. His use of paintings by Hans Holbein, Claude Lorrain, and Raphael in terms of the sublime and beautiful exemplify an understanding of Holy Saturday and its status between death and resurrection. Julia Kristeva's reading of Dostoevsky's melancholy as exemplifying a religious ideal and William Desmond's metaxological philosophy allows us to propose a terminology that rhymes with Dostoevskian between-ness, a conclusion that does not resolve the space between the beautiful and the sublime but remains open to the confessional enigmatic liminality that is Holy Saturday.